Sources of tolerance towards corrupted politicians in Greece: the role of trade offs and individual benefits - Konstantinidis, Iannis (Crime, law and social change, 2013)
Reelection of corrupted politicians points to a problem of democratic accountability. Voters do have the chance to ‘throw the rascals out’, but they do not take it. Employing a survey experiment, we test two popular explanations of why Greek voters fail to effectively sanction corrupt politicians. One is related to the distorting effects of psychological attachment to parties and the second to tradeoffs that seem to come into play when voters weigh the prevalence of corruption against other tangible benefits that they receive from governments and parties, such as lower taxes or clientelistic exchanges. Our findings suggest that collective benefits, such as cutting taxes, outweigh the costs of tolerating political corruption. On the contrary, exclusive provision of goods to specific voters, such as in the case of clientelistic exchanges, seems to be negatively related to support for a corrupt politician and therefore should rather not be regarded as a source of tolerance to corruption, at least not in present time Greece.